Aging with Resilience: Lived Experiences, Health Transitions, and Financial Challenges of Retirees in the Philippines - Saragcon, Shirley; Eden, Joshua Jay (Journal of Interdisciplinary Perspectives, 2026)
This study explored the lived experiences of Filipino retirees as they navigated health changes, financial challenges, healthcare access, and coping strategies after leaving the workforce. Using a qualitative research design, semi structured interviews were conducted with seven retirees, and their narratives were analyzed thematically. Findings revealed that retirement brought mixed health outcomes: while some experienced improved mental well-being due to reduced work-related stress, others struggled with chronic conditions such as hypertension, arthritis, and diabetes, prompting consistent self-care practices involving maintenance medication, healthy eating, and light physical activity. Financial constraints emerged as a central concern, with most retirees relying on modest pensions, strict budgeting, and family support to meet daily needs, only to have those resources disrupted by unexpected medical expenses. Access to healthcare remained difficult due to overcrowded public facilities, costly private consultations, and inconsistent availability of affordable medicines, heightening retirees’ vulnerability. Despite these challenges, participants demonstrated strong resilience rooted in faith, contentment, and supportive family relationships, viewing retirement as not only a demanding transition but also a meaningful period for reflection, simplicity, and renewed purpose. The study underscores that successful aging in the Philippine context is shaped not only by health and financial security but also by emotional stability, spirituality, and social connectedness. It highlights the need for strengthened social protection systems, improved access to affordable healthcare, and community based programs that promote dignity, autonomy, and holistic well-being among Filipino retirees.